Developmental coordination disorder and dysgraphia: signs and symptoms, diagnosis, and rehabilitation - Maëlle Biotteau; Jérémy Danna; Éloïse Baudou; Frédéric Puyjarinet; Jean‐Luc Velay; Jean‐Michel Albaret; Yves Chaix (2019)
Abstract: Developmental coordination disorder (DCD) is a common and well-recognized neurodevelopmental disorder affecting approximately 5 in every 100 individuals worldwide. It has long been included in standard national and international classifications of disorders (especially the Diagnostic and Statistical Manual of Mental Disorders ). Children and adults with DCD may come to medical or paramedical attention because of poor motor skills, poor motor coordination, and/or impaired procedural learning affecting activities of daily living. Studies show DCD persistence of 30–70% in adulthood for individuals who were diagnosed with DCD as children, with direct consequences in the academic realm and even beyond. In particular, individuals with DCD are at increased risk of impaired handwriting skills. Medium-term and long-term prognosis depends on the timing of the diagnosis, (possible) comorbid disorders (and their diagnosis), the variability of signs and symptoms (number and intensity), and the nature and frequency of the interventions individuals receive. We therefore chose to investigate the signs and symptoms, diagnosis, and rehabilitation of both DCD and developmental dysgraphia, which continues to receive far too little attention in its own right from researchers and clinicians. Keywords: developmental coordination disorder, developmental dysgraphia, clinical expressions, diagnosis, therapy, assessment tools